SplicingTypesAnno: Annotating and quantifying alternative splicing events for RNA-Seq data. Issue 1 (April 2015) - Sun, Xiaoyong; Zuo, Fenghua; Ru, Yuanbin; Guo, Jiqiang; Yan, Xiaoyan; Sablok, Gaurav
Highlights User friendly R-package for identifcation, annotating and analyzing alternative splicing events from RNA-Seq. Provide annotation for major alternative splicing at exon/intron level and identifies novel alternative splicing events using the GTF/GFF file. Generates user-friendly web report and additional BED files for IGV visualization. Provides comprehensive genome scale analysis for users with High Performance Computing (HPC) and Gene-level analysis for memory efficient personal computers.